The “all-on-four” treatment as a solution in dental implants - Falcón-Guerrero, Britto Ebert (2023)
The present report is intended to reach an idea about the “All-On-Four” treatment, about the simple of the clinical procedure and the pro and cons that they give to do; focusing mainly on the indications of treatment, surgical procedures and prosthetic protocols, and secondly on the mechanical and biological complications involved. A search was executed in Pubmed and Cochrane, with the descriptors ("All-on-Four"), ("Dental Implants"), ("Complication of All-On-Four"), ("Management of All-On-Four") and ("Techniques "), Where the research works evidenced by the prosthetic and surgical approach of the "All-On-Four" implants, as well as their consequences, was analyzed. The “All-On-Four” treatment objective is to evaluate the survival rate of the implants to rehabilitate maxillary and completely edentulum jaw.